THE EVOLUTION OF E-BANKING: CHALLENGES AND OPPORTUNITIES IN INDIA - Muhammed Juman B K , Dr.J Christopher (International Journal of Research Science and Management, 2015)
India is still in the early stages of E Banking growth and development. Competition and changes in technology and lifestyle in the last 15 years have changed the face of Banking. Today banking is known as innovative banking. Indian banking industry is the midst of an IT revolution. E- Banking, i.e. banking through electronic channels has gained increasing popularity in recent years. This system provides alternatives for faster delivery of banking services to a wide range of customers. Productivity enhancement, innovative products, speedy transactions seamless transfer of funds, real time information system, and efficient risk management are some of the advantage derived through the technology. Information technology has also improved the efficiency and robustness of business processes across banking sector. This study aims the concept and Scope of E Banking is still evolving several initiatives taken by Government of India as well as Country’s Central Bank, the Reserve Bank of India have facilitated the development of E-Banking in India. This paper aims to present the E-Banking challenges and opportunities in India.